Diversity of bird species in paddy habitat in Alus-alus of Simeulue Regency - Rika Susanti; Abdullah Abdullah; Devi Syafrianti; Muhibbuddin Muhibbuddin; Khairil Khairil (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2020)
Research entitled "Diversity of bird species in paddy habitat in Alus-alus of Simeulue Regency". The purpose of this study was to study the types and levels of variation of bird species in their paddy habitat and dominance. The method applied in this study is the IPA (Point Abundance Index) method, which is by collecting the types of birds found in each observation area. The parameters examined in this study are the types of birds, the index of variation and the dominant bird species in paddy habitat in Alus-alus Village, Simeulue Regency. Analysis of the data in this study using the Shannon-Weaver collection index formula, analyzed in full and explained with tables and graphs. The results of this study are approximately 22 species of birds from 16 families. The level of variation of bird species found in paddy habitat in the Alus-alus Village Region of Simeulue Regency is classified as moderate with its diversity index being H '= 2.9492. The types of birds that dominate in the habitat of paddy are Lonchura maja birds. The conclusion in this study is the index in the habitat of paddy fields with H '= 2.3542. The type of bird that denies in the paddy habitat that was moved by the Lonchura maja bird. Keywords: Bird diversity, species, habitat.Penelitian yang berjudul “Keanekaragaman Jenis-jenis burung pada habitat persawahan di Kawasan Desa Alus-alus Kabupaten Simeulue”. Tujuan penelitian ini adalah untuk mempelajari jenis-jenis dan tingkat variasi jenis burung di habitat persawahan dan dominansinya. Metode yang diterapkan dalam penelitian ini ialah metode IPA (Indeks Point Abundance), ialah dengan melakukan pendataan jenis-jenis burung yang dijumpai pada setiap kawasan pengamatan. Parameter yang diteliti dalam penelitian ini ialah jenis-jenis burung, Indeks variasi dan jenis burung dominan di habitat persawahan di Desa Alus-alus, Kabupaten Simeulue. Analisis data dalam penelitian ini dengan menggunakan rumus indeks koleksi Shannon-Weaver, dianalisis secara lengkap dan diterangkan dengan bentuk tabel dan grafik. Hasil penelitian ini ialah kira-kira 22 jenis burung dari 16 famili. Tingkat variasi jenis burung yang terdapat di habitat persawahan di Kawasan Desa Alus-alus Kabupaten Simeulue tergolong sedang dengan indeks keanekaragamannya adalah H '= 2,9492. Jenis-jenis burung yang mendominansi di habitat Persawahan ialah burung Lonchura maja. Kesimpulan dalam penelitian ini adalah indeks pada habitat Persawahan dengan H '= 2.3542. Jenis burung yang membantah di habitat Persawahan yang dipindahkan oleh burung Lonchura maja. Kata Kunci: Keanekaragaman burung, jenis-jenis, habitat